Introducing restorative practices into high schools' multi-tiered systems of support: successes and challenges. Issue 4 (2nd October 2021) - Vincent, Claudia; Inglish, John; Girvan, Erik; Van Ryzin, Mark; Svanks, Rita; Springer, Shareen; Ivey, Allison
ABSTRACT: We report findings from a recent field test assessing the feasibility of training teachers in implementing restorative practices within a multi-tiered approach to supporting student behavior. First, we provide an overview of our training content, training delivery, and follow-up coaching. Second, we present overall outcomes from our field test with three non-traditional high schools. Results indicated improvements in overall school-wide implementation of restorative consequences, and gains in teacher use of existing discipline approaches as well as restorative practices. Results also indicated increases in early adopters' confidence level with motivating students and engaging them in appropriate behavior across the duration of the study. Challenges associated with implementation included aligning administrative commitments to restorative practices with individual teachers' willingness to change classroom practices, allocating sufficient time to change policies and practices and overcoming logistical challenges to maximize coaching benefits. Finally, we discuss our field test findings within the current recommendations for advancing the evidence-based supporting restorative practices in schools.